Aplikasi Pencarian Rute Terdekat Tempat Dokter Praktek Fasilitas Bpjs Mengunakan Metode Djikstra - Luviani, Luviani; Apriyanto Alhamad; Serwin; Mohamad Efendi Lasulika (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2024)
Abstract- Searching for the fastest route while traveling is necessary besides finding the destination. The reason for finding the fastest route is to streamline the trip and save travel costs. Another problem in making an effective trip is a city search carried out by someone who knows, someone who spreads hospitals, health centers, clinics, and pharmacies that serve the Social Insurance Administration Organization in Gorontalo City/Regency, and knows several nearby places. In the implementation of the Social Insurance Administration Organization in Gorontalo City/Regency branch, there are still obstacles faced by the community. The lack of information regarding the distribution of health facilities and information makes people confused when choosing and locating which health facility they will visit for treatment using a card from the Social Insurance Administration Organization. By designing this information system, people can map the health facilities that serve the Social Insurance Administration Organization. The designation of this system uses the DJikstra algorithm to find the fastest route to the health facilities of Social Insurance Administration Organization to obtain a research result of a system that can find the fastest route to the health facilities of the Social Insurance Administration Organization. It is hoped that it can help the public in getting the fastest way to health facilities of the Social Insurance Administration Organization in Gorontalo City/Regency. Keywords: fastest route search system, health facilities, Social Insurance Administration Organization, Djikstra algorithm